Plasmodium falciparum var Gene Silencing Is Determined by cis DNA Elements That Form Stable and Heritable Interactions - Swamy, Lakshmi (American Society for Microbiology, 2011)

(untitled)
Antigenic variation in the human malaria parasite Plasmodium falciparum depends on the transcriptional regulation of the var gene family. In each individual parasite, mRNA is expressed exclusively from 1 var gene out of ∼60, while the rest of the genes are transcriptionally silenced. Both modifications to chromatin structure and DNA regulatory elements associated with each var gene have been implicated in the organization and maintenance of the silent state. Whether silencing is established at the level of entire chromosomal regions via heterochromatin spreading or at the level of individual var promoters through the action of a silencing element within each var intron has been debated. Here, we consider both possibilities, using clonal parasite lines carrying chromosomally integrated transgenes. We confirm a previous finding that the loss of an adjacent var intron results in var promoter activation and further show that transcriptional activation of a var promoter within a cluster does not affect the transcriptional activity of neighboring var promoters. Our results provide more evidence for the hypothesis that var genes are primarily silenced at the level of an individual gene, rather than by heterochromatin spreading. We also tested the intrinsic directionality of an intron's silencing effect on upstream or downstream var promoters. We found that an intron is capable of silencing in either direction and that, once established, a var promoter-intron pair is stably maintained through many generations, suggesting a possible role in epigenetic memory. This study provides insights into the regulation of endogenous var gene clusters.